Factors associated with eating disorders in university students in Cali, Colombia. (Colombia Medica, 2007)
Introduction: There are few studies about eating disorders (ED) in adolescents and young adults in Latin America. Moreover, socio-demographic characteristics of university students suggest they may experience cases of ED in a percentage greater than general population’s one.Objective: To determine the percentage of students with high risk of developing altered eating behaviours, and to estimate the prevalence of ED in that population. Additionally, to examine factors associated with a positive outcome in a screening test for ED. Methods: A cross-sectional study was conducted in 174 students of first and second year of Medicine at Universidad del Valle (Cali, Colombia), who completed a self-reported questionnaire with the test for Evaluation of Eating Behaviour (EEV). Results: The 39.7% of students had positive scores in the EEV (>24), which is indicative of high risk of suffering an Eating Disorder (ED); with a 2/1 woman/man ratio and an estimated prevalence of ED of 44.1% in women and of 9.6% in men. The associated factors for positive outcomes in the EEV are female gender (OR: 2.74 CI95%: 1.29-5.85), desire for losing more than 10% of body weight (OR: 24.65 CI95%: 1.92-316.91), and interaction between the last factor and the desired percentage of weight loss (OR: 0.81 CI95%: 0.66-0.98). There is a qualitative interaction between the direction of desired weight loss and other variables in the model. Discussion and conclusions: The EEV identifies different kinds of ED which should be differentiated by additional questions. The estimated prevalence of ED shows that it is an important problem in the university community, which should be tackled by means of different prevention, early detection and treatment strategies.